Ash melting behavior and slag infiltration into alumina refractory simulating co-gasification of coal and biomass. (1st January 2015) - Zhang, Guanjun; Reinmöller, Markus; Klinger, Mathias; Meyer, Bernd
Highlights: Ash melting behavior of coal and biomass blends varies strongly from the pure fuels. Slag wetting properties on alumina refractory are obviously influenced by blending. Slag infiltrates pores and binder matrix, while alumina grains are more resistant. Thermochemical modeling may be utilized to describe slag infiltration depth. Slags from blends feature higher corrosion potential than those from pure fuels. Abstract: In the present study melting behavior of ashes from German brown coal and biomass (wheat straw) as well as from two artificial mixtures of both has been investigated. The four fuel samples were ashed at 450 °C over a period of 26 h. Ash fusion tests and all other measurements have been executed under reducing atmosphere, simulating gasification conditions. The ash melting and wetting properties have been studied for ash cylinders placed onto an alumina refractory at temperatures up to 1600 °C. Optical microscopy and SEM/EDX studies have been performed to analyze the infiltration of slag into the refractory and related progression. For the ash fusion behavior and surface wetting of the refractory clear distinctions from pure ashes have been detected for the blend with 50 wt.% biomass addition due to the formation of eutectics. From optical microscopy and SEM/EDX images of the sections different infiltration properties and mechanisms have been identified. The qualitative infiltration depth and deceleration of slag infiltration by a formation of solid phases have been provided by FactSage™ calculations. In these calculations the contact zone between the two materials has been reconstructed by a stepwise change in the amounts of ash and refractory. The experimental results are very well reflected in this model. Finally, the obtained results suggest low corrosive biomass amounts for co-use in the present gasifier types designed for pure coal.